Synthesis of task specific and reusable protic ionic liquids for one-pot multicomponent syntheses - Sardar, S. (American Institute of Physics Inc., 2016)
Protic ionic liquids (ILs) synthesized from 1-methylimidazole with 1,3-propane sultone and 1,4-butane sultone catalyzed Mannich reaction at 25Â°C to afford Mannich bases in high yield (76) and less time duration (20 min). Ionic liquids have been used as dual reagent i.e., as catalyst as well as solvent. Simple extraction by water separated ionic liquid from reaction mixture with 4 times recycling without any significant loss in activity. Â© 2016 Author(s).